1996
DOI: 10.1097/00005392-199612000-00054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tadenan Pretreatment on Bladder Physiology and Biochemistry Following Partial Outlet Obstruction

Abstract: These results clearly demonstrate that Tadenan pretreatment protected the bladder from both the contractile and metabolic dysfunctions induced by partial outlet obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…However, we have extensive experience with this model, and based on the performance of hundreds of similar studies, in the mild model of obstruction there is always a marked decrease in compliance and a significant reduction in the contractile response to field stimulation at 2 weeks following obstruction [Kato et al, 1988[Kato et al, , 1990b. Similarly, in the severe model, at 2 weeks following obstruction there is always a marked reduction in the contractile responses to both field stimulation and bethanechol [Malkowicz et al, 1986;Levin et al, 1996b]. Following the initial 2-week period, there is either no further change or a progressive decrease in the contractile responses over the next several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have extensive experience with this model, and based on the performance of hundreds of similar studies, in the mild model of obstruction there is always a marked decrease in compliance and a significant reduction in the contractile response to field stimulation at 2 weeks following obstruction [Kato et al, 1988[Kato et al, , 1990b. Similarly, in the severe model, at 2 weeks following obstruction there is always a marked reduction in the contractile responses to both field stimulation and bethanechol [Malkowicz et al, 1986;Levin et al, 1996b]. Following the initial 2-week period, there is either no further change or a progressive decrease in the contractile responses over the next several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreating rabbits with Pygeum africanum (Tadenan) for 3 weeks before the surgical creation of partial outlet obstruction prevented the development of the initial contractile and metabolic dysfunctions. Results of subsequent studies showed that treating rabbits previously subjected to partial outlet obstruction reversed decompensation and resulted in improved contractile function [Levin et al, 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Partial outlet obstruction and in vivo models of ischemia have marked deleterious effects on superoxide dismutase and catalase, and as stated above have also been demonstrated to produce significant oxidative damage (10,(12)(13)(14). A variety of antioxidants and natural products that show significant antioxidant properties have been shown to protect the rabbit urinary bladder from contractile, cellular, and subcellular damage and dysfunction mediated by both partial outlet obstruction, and bilateral ischemia / reperfusion (15)(16)(17)(18)(19)(20). One of the most potent of these agents has been shown to be a grape suspension made from whole grapes (13,21,22).…”
Section: Introductionmentioning
confidence: 93%